2023
DOI: 10.3390/ijms24065237
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and Saliva Extracellular Vesicles for Biomarker Candidate Identification—Assay Development and Pilot Study in Amyotrophic Lateral Sclerosis

Abstract: Saliva is gaining increasing attention as a source of biomarkers due to non-invasive and undemanding collection access. Extracellular vesicles (EVs) are nano-sized, cell-released particles that contain molecular information about their parent cells. In this study, we developed methods for saliva biomarker candidate identification using EV-isolation and proteomic evaluation. We used pooled saliva samples for assay development. EVs were isolated using membrane affinity-based methods followed by their characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…While the natural concentration of native EVs in saliva is not known, various studies estimate a range 1 or 2 orders of magnitude greater than the present sensitivity achieved. 49,50 Interestingly, a rapid uptake is visible over the first 5−10 min, followed by a slower uptake also present in the control experiment (pure saliva). This suggests that a quantitative readout is possible in less than 30 min despite the small sample volume and the absence of any sample preparation or conditioning of the sample.…”
Section: T H I S C O N T E N T Imentioning
confidence: 68%
“…While the natural concentration of native EVs in saliva is not known, various studies estimate a range 1 or 2 orders of magnitude greater than the present sensitivity achieved. 49,50 Interestingly, a rapid uptake is visible over the first 5−10 min, followed by a slower uptake also present in the control experiment (pure saliva). This suggests that a quantitative readout is possible in less than 30 min despite the small sample volume and the absence of any sample preparation or conditioning of the sample.…”
Section: T H I S C O N T E N T Imentioning
confidence: 68%
“…Sjoqvist et al established a workflow for the analysis of saliva and sEVs to compare protein profiles between ALS patients and healthy individuals. The study revealed a downregulation trend in ZNF428 (zinc finger protein 428) in sEVs from ALS patients compared with the control group [144].…”
Section: Neurodegenerative Diseasesmentioning
confidence: 81%
“…Salivary EVs have immense potential as biomarkers of non-communicable chronic diseases [ 26 , 27 , 28 ], due to their non-invasive and relatively simple collection methods and to the ability of EVs to cross epithelial barriers [ 29 , 30 , 31 ] and reach the salivary glands via peripheral blood [ 32 ]. However, the lack of studies assessing the efficiency and purity of different EV isolation techniques hinders the use of salivary EVs in clinical settings.…”
Section: Discussionmentioning
confidence: 99%